Citizen Science Project, Weather-it, in Science Education: The Scientific Attitudes of Junior High School Students - St E Sururiyatul Muaziyah; Topik Hidayat; Siti Sriyati; Lia Lutianasari (Universitas Khairun, 2023)
Formal education increasingly includes citizen science projects. There is clear evidence of the benefits of citizen science projects for science learning, where one of the goals of science education is to foster a logical mindset and add information to students. This study aimed to measure changes in scientific attitude and the addition of knowledge acquired by students. This project is named Weather-it, which consists of activities to investigate the weather and identify clouds. Thirty junior high school students were involved in this study. Research data were obtained from semi-structured interviews and questionnaires. The experts have verified the 23 statement items on the questionnaire sheet. The results showed that 77% of students were in the good category for the indicator of curiosity, 67% in the sufficient category for the indicator of respect for data, 93% for the sufficient category for the indicator of critical thinking, and 77% for the sufficient category for the indicator of open-mindedness and cooperation. Furthermore, students explained the knowledge they gained through the citizen science project, Weather-it, including knowledge about clouds, technology, the use of Microsoft Excel in processing data, the use of weather in aviation, and the duties of a meteorologist.